Understanding the public debate about trophy hunting in China as a rural development mechanism. (24th September 2020) - Zhou, X.; MacMillan, D. C.; Zhang, W.; Wang, Q.; Jin, Y.; Verissimo, D.
Abstract: The use of trophy hunting as a wildlife management option has been a highly controversial topic, especially in southern Africa, but trophy hunting has historically also taken place also throughout Asia. In China, trophy hunting was the topic of intense public discussion more than a decade ago, leading ultimately to the suspension of this practice in 2006. Yet, this debate was dominated by urban voices, with no formal consultation of rural populations from minorities such as the Tibetan herders who previously benefited financially from commercial trophy hunting acting as guides and who are also concerned about the negative impact of rising blue sheep numbers on livestock grazing. We used a discrete choice experiment econometric method to better understand the trade‐offs made by both urban and rural populations across China in relation trophy hunting as a rural development and wildlife management tool. We find that trophy hunting is supported by the majority of rural residents but opposed by most urban residents, although there is heterogeneity within both these groups. We recommend that policy‐making in this realm should be informed by a better understanding of the preferences of different stakeholders, including the local people who bear the costs of living with wildlife. Abstract : In China, trophy hunting was the topic of intense public discussion more than a decade ago, leading ultimately to the suspension of this practice in 2006. Yet, this debate was dominated by urban voices, with no formal consultation of rural populations from minorities such as the Tibetan herders. We found that trophy hunting in China is supported by the majority of rural residents but opposed by most urban residents. It is key that communities living with wildlife are consulted when decision about wildlife management are made.